Impact of glucocorticoids and rapamycin on autophagy in Candida glabrata-infected macrophages from BALB/c mice - Yang, Zhenghui; Wang, Xinyi; Dong, Tianxiang; Zhao, Wei-Jia; Li, Hongbin (Frontiers in Immunology, 2024)
Objective: In the defense against microorganisms like Candida albicans, macrophages recruit LC3(Microtubule-associated protein 1A/1B-light chain 3) to the periplasm, engaging in the elimination process through the formation of a single-membrane phagosome known as LC3-associated phagocytosis (LAP) [1].Building on this, we propose the hypothesis that glucocorticoids may hinder macrophage phagocytosis of Candida glabrata by suppressing LAP, and rapamycin could potentially reverse this inhibitory effect. Methods: RAW264.7 cells were employed for investigating the immune response to Candida glabrata infection.Various reagents, including dexamethasone, rapamycin, and specific antibodies, were utilized in experimental setups. Assays, such as fluorescence microscopy, flow cytometry, ELISA (Enzyme-Linked Immunosorbent Assay), Western blot, and confocal microscopy, were conducted to assess phagocytosis, cytokine levels, protein expression, viability, and autophagy dynamics. Results: Glucocorticoids significantly inhibited macrophage autophagy, impairing the cells' ability to combat Candida glabrata. Conversely, rapamycin exhibited a dual role, initially inhibiting and subsequently promoting phagocytosis of Candida glabrata by macrophages.Glucocorticoids hinder macrophage autophagy in Candida glabrata infection by suppressing the MTOR pathway(mammalian target of rapamycin pathway), while the activation of MTOR pathway by Candida glabrata diminishes over time. Conclusions:Our study elucidates the intricate interplay between glucocorticoids, rapamycin, and macrophage autophagy during Candida glabrata infection.Understanding the implications of these interactions not only sheds light on the host immune response dynamics but also unveils potential therapeutic avenues for managing fungal infections.